Random Early Detection method for ABR service - Hosamo, Mohsen; Singh, S.P.; Mohan, Anand (Computers & electrical engineering, 2008)
A new implementation for the Random Early Detection method algorithm for ABR (REDM–ABR) service is proposed in this paper. It keeps running an exponential average of the queue length ( Q). When a cell arrives, the average queue size ( Q avg) is compared with two threshold levels, lower queue threshold ( Q L) and higher queue threshold ( Q H). If it is smaller than Q L, the cell is passed, but if it is larger than Q H, the cell marking probability is set to one. If it is in between the two thresholds, the cell marking probability is calculated depending on the value of Q avg. The values of Resource Management (RM) cell fields: Congestion Indication (CI), No Additive Increase (NI), and Explicit Rate (ER) are filled by the Relative Rate Marking (RRM) switch and sent back to the sources. The sources will change their rate depending on CI, NI, and ER values. To investigate the effect of decreasing the impending congestion area, a dynamic Q threshold ( Q D) is used. The Q D is shifted from Q L toward Q H for decreasing the congestion area and to investigate the effect of this shift on the performance of the switch through simulation study.